Anchor Heave-Up Failure of MV. Warih Mas in Palu Bay: Kegagalan Heave-Up Jangkar pada MV. Warih Mas di Teluk Palu - Prayogi, Lilik; Siregar, Muhammad Sapril; Nurmala, Eka (ATRIA: Jurnal Multidisiplin Riset Ilmiah, 2024)
Shipping safety is important not only when docked at the port or when the ship is sailing but also when the ship is at anchor. This study aims to determine the cause of the anchor heave-up failure of MV Warih Mas in Palu Bay and to explore factors, strategies, and maintenance practices related to anchor equipment on the ship. The study uses a qualitative approach, and the data will be presented through descriptive analysis. The study participants include the ship's master and crew. Data collection methods include direct observation, in-depth interviews, and documentation studies, while data analysis consists of three stages: data reduction, data presentation, and verification. The results indicate that the cause of the failure was corrosion of the anchor chain due to prolonged exposure to water in the chain locker. Three strategies were attempted, but only one was successful: Inserting iron into the chain link of the anchor on the windlass drum to allow the chain to rotate. The crew did not carry out maintenance on the anchor equipment, possibly due to a lack of skills and training.